An Act in relation to the Indian tribe in this state
January 29, 1840 Bill which appointed a Commissioner of the Narragansett Indian Tribe. The position would be appointed by the governor to supervise and determine all controversies, bring actions in his hand, and otherwise enforce the laws regarding the tribe.